Rapid, Simple, and Highly Specific Detection of Streptococcus pneumoniae With Visualized Recombinase Polymerase Amplification - Wang, Fang; Wang, Yan; Liu, Xia; Wang, Lei; Wang, Kun; Xu, Chenglai; Huang, Guanhong; Gao, Xuzhu (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract: Streptococcus pneumoniae is a major pathogen that causes microbiological illness in humans. The introduction of polyvalent vaccines has resulted in a significant decrease in pneumococcal-related mortality. However, pneumococcal infections continue to be a leading cause of death in children under the age of 5 and adults over the age of 65 worldwide. A speedy and highly sensitive diagnostic tool is necessary for routine adoption to adequately manage patients and control the spread of infection. In this study, we investigated a new nucleic acid amplification technique, isothermal recombinase polymerase amplification (RPA), which amplifies DNA at 37°C under isothermal conditions with high specificity, efficiency, and rapidity. Using the autolysin gene lytA as the molecular diagnostic target, an RPA primer-probe combination was designed and optimized for the detection of S. pneumoniae. This RPA reaction produced amplification products labeled with specific chemical markers, to be detected with gold-nanoparticle-based lateral flow strips (LFS), reducing the reliance on equipment and trained personnel. The high specificity of the RPA-LFS technique was demonstrated with the specific detection of 22 strains of S. pneumoniae but not 25 closely related pathogenic bacteria. The assay showed good sensitivity, and detected S. pneumoniae down to 3.32 colony-forming units/μL. When used on clinical samples, the assay provided accurate and consistent results compared with PCR. The compliance with the culture-biochemistry method was 98.18% and the kappa index was 0.977. These results reveal that the RPA–LFS test significantly improved S. pneumoniae identification, particularly in resource-limited areas.